A model for full-blown implementation of lean manufacturing system in Malaysian automative industry / Eida Nadirah Roslin - Eida Nadirah , Roslin (2013)
Lean manufacturing strategy is one of the known systems that are acknowledged to be capable and effective towards achieving tremendous growth and improvement. Implementations of lean within the automotive industry in Malaysia is not far-reaching as expected and is currently being adopted as a pick-and-choose system and being applied only in certain stages and known areas. This approach does not allow these organizations to fully explore and exploit the system‟s effectiveness; neither do they experience any massive improvements when measured against lean manufacturing success standards. Moreover, factors affecting the lean manufacturing implementation in Malaysia is still seldom debated or being discussed extensively in many other available in literature reviews. This study attempts, as its main objective, to develop a model for implementation of Lean Manufacturing System (LMS) within the manufacturing industry in Malaysia, specifically for the automotive parts manufacturing industry. This model would act as a comprehensive guideline for LMS implementation within an organization. The model was tested empirically and verified by using SEM model validation processes. A questionnaire-survey was administered to gauge levels of LMS adoption, utilization and acceptance in local outfits. The data were collected from about 200 automotive parts manufacturing companies over a period of six months with the collaboration of Malaysia Automotive Institute (MAI), a Malaysian government agency under MITI (Ministry of Trade and Industry). The data was then analyzed using the Structural Equation Modeling (SEM) software and the SPSS version 20 software. The results suggest that with LMS firms can develop a valuable key organizational capability in a more flexible manner where a firm‟s performance can be predicted and positive results materialize. The results from the SEM analysis demonstrated that effective implementation of LMS can influence all the six (6) dimensions of known manufacturing efficiency tools and business performances indicators positively. It was particularly observed that waste in multiple levels within an organization can be reduced to bring about most significant expected benefits of LMS implementation for Malaysian automotive parts manufacturers which, respectively, is followed by other expected beneficial gains such as engineering performances, operational performance, non-financial performance, marketing performance, and financial performance. Although the in-depth regression analysis showed that even the effective implementation of a single lean tool such as just in time can result in significant performance improvements for a firm in question, however, the structural mode revealed that different tools of LMS mutually support and reinforce each other and the joint value of complementary LMS tools is significantly greater than the sum of their individual values. Thus LMS complementarily creates super-additive value synergy. The presented model of LMS implementation and relative findings are expected to offer valuable insights to practicing managers, lean experts, and policy makers responsible for assisting Malaysian automotive parts manufacturers with the full-blown of LMS implementation. Additionally, the model and findings of this study can serve as a benchmark measure of factors that can facilitate effective LMS implementation for future researchers in which, the same population, or others, at different industries, country, and times in the future can be accordingly replicated. Keywords: LMS, Full-blown Model, Automotive industry, Operational Performances, Operational Standards